Tolerance and safety of adenosine stress perfusion cardiovascular magnetic resonance imaging in patients with severe coronary artery disease - Karamitsos, T; Arnold, JR; Pegg, T; Cheng, A; van Gaal, W; Francis, J; Banning, A; Neubauer, S; Selvanayagam, J (Springer Netherlands, 2009)
We sought to assess the tolerance and safety of adenosine-stress cardiovascular magnetic resonance (CMR) perfusion imaging in patients with coronary artery disease (CAD). We retrospectively examined all adenosine CMR perfusion scans performed in our centre in patients with known or suspected (CAD) and normal volunteers at either 1.5 or 3 T. All subjects were initially screened for contraindications to adenosine. The dose of adenosine infused was 140 μg/kg/min. Significant CAD was defined angiographically as the presence of at least one stenosis of >50% diameter. Data were collected from 351 consecutive subjects (mean age 62 ± 11 years, range 25-85 years-245 men). Of the 351 subjects, 305 had a coronary angiogram, the remaining 46 subjects were normal volunteers studied for research protocols. In total, 233 subjects (76%) were found to have significant CAD of whom 128 had multi-vessel disease. There were no deaths, myocardial infarctions, or episodes of bronchospasm during the CMR study. Transient 2nd (Mobitz II) or 3rd-degree atrioventricular (AV) block occurred in 27 patients (8%). There were no sustained episodes of advanced AV block. Transient chest pain was the most common side effect (199 subjects-57%). The use of intravenous adenosine in CMR perfusion imaging is safe and well-tolerated, even in patients with severe CAD. Where a careful screening policy for contraindications to adenosine is followed, serious adverse events in the CMR scanner are relatively rare and symptoms resolve following termination of the infusion, without the need for aminophylline. © 2008 Springer Science+Business Media, B.V.